Isokinetic muscle strength and running long jump performance in young jumpers - Koutsioras, Y.; Tsiokanos, A.; Tsaopoulos, D.; Tsimeas, P. (Biology of Exercise, 2009)
The aim of this study was two-fold. Firstly we wanted to quantify the relationship of isokinetic muscle strength (IMS) and long jump performance (LJP) in young jumpers, and secondly to compare males and females in IMS. Our measurements in 7 males and 7 females showed that the LJP was correlated with the normalized peak joint moment of the concentric knee extensions and the concentric ankle plantar flexions. A low correlation was observed between the LJP and the eccentric knee extensions. The t-test showed significant gender differences in joint peak moment of concentric knee extensions and in normalized peak joint moment of concentric plantar flexions and eccentric plantar flexions at 120 deg /sec. Although, our findings suggest that IMS is a major contributor to LJP, it is suggested that training intervention should not be based exclusively on isokinetic tests because of the differences in musculoskeletal function between the two movements.